Traditional handicrafts and the use of natural resources among the Iban of Balai Ringin, Serian, - Larry Sait, Eva Kristin; Mersat, Neilson Ilan; Wong, Swee Kiong (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study investigates the possible gaps in current indigenous knowledge in the use of natural resources, specifically in traditional handicraft making. The Iban women are known for their traditional weaving skills. However, due to various reasons, this knowledge is declining. Through interviews and focus group discussions, the knowledge on the types and availability of resources in the respective areas, as well as the gap of knowledge in resource use and management between the older and younger generations and its cause were identified. Through observation, while traditional baskets and mats are still used by the Iban today, most of the traditional handicrafts made using natural materials seen in the longhouses are relics from the past, made by previous generations. The scarcity of raw materials such as rattan and wood has resulted in the decline of the production of such handicrafts. Though the skills of making these baskets especially among younger generation are eroding, the cultural significance of this basket among Iban community should not be forgotten.